2018
DOI: 10.26636/jtit.2018.125418
|View full text |Cite
|
Sign up to set email alerts
|

Interference Management using Power Control for Device-to-Device Communication in Future Cellular Network

Abstract: There are many scenarios that have been proposed for fifth generation (5G) networks. Some of them, if implemented, will bring fundamental changes at the architectural and node level. One example of such proposed technologies is device-to-device (D2D) communications which will change the nature of conventional cellular network design. D2D permits direct communication between two or more user devices without intervention of the base station (i.e. eNB). D2D can ensure network performance improvement over the tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…It was observed that as the numbers of D2D pairs are increasing for all investigated techniques, SINR is decreasing. As observed in Figure 6, Comparison among the average SINR obtained for all the techniques deployed shows that the RPTC,APTC and OPTC technique has higher values for different numbers of D2D pairs, unlike the FPTC which performed poorly as confirmed by [36], [39]. It may be noted that, these techniques are able to contain SINR performance ability, they may perform because of the ability of individual transmitter of devices been able to realign with power of transmitter relative to the calculated SINR and interference parameters as observed by [38].…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…It was observed that as the numbers of D2D pairs are increasing for all investigated techniques, SINR is decreasing. As observed in Figure 6, Comparison among the average SINR obtained for all the techniques deployed shows that the RPTC,APTC and OPTC technique has higher values for different numbers of D2D pairs, unlike the FPTC which performed poorly as confirmed by [36], [39]. It may be noted that, these techniques are able to contain SINR performance ability, they may perform because of the ability of individual transmitter of devices been able to realign with power of transmitter relative to the calculated SINR and interference parameters as observed by [38].…”
Section: Resultsmentioning
confidence: 64%
“…With due recognition of the representation obtained when addressed with respect numbers of device pairs as regards the comparison of the value of the SINR obtained for the techniques used, it becomes indisputable and worthy of note that the respective values of the various techniques have higher values for different respective numbers of D2D pairs for the RPTC,APTC and OPTC. However, in the case of the FPTC which performed poorly and this of course is a reflection of its inability to conform to the signal to interference ratio of noise when varied with a referenced distance as confirmed in the previous work done by [36], [39] when compared to other techniques. In a related development, these techniques generally, as seen by their performance they are able to contain SINR performance ability, because of the ability of the individual transmitter of devices have been able to realign with the power of transmitter relative to the calculated SINR and interference parameters.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Several frameworks have been proposed for interference management by means of transmission power control in D2D communication systems. These frameworks can be broadly categorized as in-band [6][7][8][9][10][11] and out-band [12][13][14][15][16]. Inband refers to the sharing of the available licensed spectrum between D2D and regular traffic.…”
Section: Introductionmentioning
confidence: 99%